1962
DOI: 10.1139/b62-123
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Growth in Marquis Wheat, as Regulated by Temperature, Light Intensity, and Daylength

Abstract: The area of a fully-grown leaf lamina varied according to its position on the stem, and the temperature, light intensity, and photoperiod under which the plant was grown.I n continuous illumination, raising the temperature by 5' intervals between 10 and 25" C, resulted in progressively higher rates of leaf initiation, emergence, and expansion. The length of the lamina increased with each increase in temperature, but the breadth and thickness decreased. The greatest area of individual leaves was formed a t 20°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 21 publications
9
48
0
Order By: Relevance
“…1) and increased amounts of dry mass accumulated (Fig. 2), which is in agreement with the findings of Friend et al (13). Tillering data are similar to the results of Evans et al (12), who found that tiller number increased linearly with increasing solar radiation.…”
Section: Results and Discussion Effect Of Radiation Intensitysupporting
confidence: 92%
See 1 more Smart Citation
“…1) and increased amounts of dry mass accumulated (Fig. 2), which is in agreement with the findings of Friend et al (13). Tillering data are similar to the results of Evans et al (12), who found that tiller number increased linearly with increasing solar radiation.…”
Section: Results and Discussion Effect Of Radiation Intensitysupporting
confidence: 92%
“…Plants grown in the reduced P treatment, therefore, did not accumulate more dry mass in response to PPF than did plants grown in other treatments. The data in Figures 1 and 2, and previous research (13), also indicate that dry mass was positively correlated with tiller production; i.e. larger plants produced more tillers (Fig.…”
Section: Results and Discussion Effect Of Radiation Intensitysupporting
confidence: 79%
“…At the later stages of crop growth, declined in CGR caused by mutual shading and leaf senescence which might reduced the photosynthetic efficiency and ultimately reduced the dry matter accumulation rate. Similar findings were also observed with different crop species by Friend et al (1962), Wall and Cartwright (1974), Stern and Kirby. (1979).…”
Section: Fig 1 Effect Of Sowing Dates On Leaf Area Index Of Bari Mosupporting
confidence: 87%
“…Indeed, at a constant temperaplants was curvilinear with temperature, with an optiture the rate of emergence of successive leaves on the mum at about 21°C. These findings were in agreement main stem of a wheat plant is constant, but the rate of with the early report by Friend et aL (1962) that leaf leaf development is different at different temperatures growth rates in wheat show a curvilinear relationship (Cao and Moss, 1989a).…”
supporting
confidence: 90%